Paleogeomorphology Reconstruction of Della Landslide and the Formation of the Shimbar Dam Lake in Indica – Khuzestan province - siyamack sharafi; masoud sadeghirad; zahra javadi nia (تحقیقات کاربردی علوم جغرافیایی, 2020)
the occurrence of landslides in the direction of rivers, especially in the mountainous regions of Zagros range are processes that block rivers and form lake barriers. Della Landslide is an example of such landslide that occurred in the course of Shimbar River drainage and eventually created Lake Shimbar. geoarchaeological field studies performed on this slide using topographic maps, geological, digital model of the area, satellite images and Arc GIS software on the  landslide and  basin lake Shimbar resulted in the identification of the causes of landslides and changes in three stages of the lake. This study eventually rebuilds Paleogeomorphology of landslide area and the lake's dam Shimbar. The results showed that the main cause of the occurrence of landslides were tectonic processes in the region and based on archaeological evidence and the archaeological excavation of the canal, the landslides occurred before 2000 years ago. The formation and changes in the scope and depth of the lake Shimbar in 3 stages blocked the migration routes in area for a long time.